Addressing inequality: Educators responding to the contexts of young children's lives?. (31st August 2020) - Nolan, Andrea
Abstract: A child's early relationships and experiences influence their long‐term development and learning. In Australia, some children can face complex levels of deprivation when compared to their peers. This study sheds light on how educators are responding. Data analysed consist of individual interviews with early childhood educators working in diverse communities. The findings highlight educators' accounts of responsiveness as narrowly framed with attention focused on children's cultural heritage which overshadows other equity groups. The paper argues that by becoming sensitive to the contexts of children's lives, there is potential to build the early childhood workforce's capacity for addressing inequalities in childhood.